An examination of the relationship between workplace support, resources and work-related well-being among Administrative, Technical Services Staff (ATSS) at The University of the West Indies - Myers-O’Connor, Aniva (My University, 2018)
Work-related well-being is a complex phenomenon which is of critical importance in this current era of economic restructuring in Trinidad and Tobago. As such, with a sample size of 120 participants, an examination of workplace support, resources and work-related well-being among the ATSS at the University of the West Indies (UWI), St. Augustine, Trinidad and Tobago was conducted. The study aimed to measure their levels of work-related well-being, explore the relative significance if any, of the aforementioned variables for understanding their levels of work-related well-being, and to make recommendations on what can be done to enhance work-related well-being among the body of ATSS. Using theoretical triangulation (with the combined examination of Job Demand-Resources Theory and Social Exchange Theory), the researcher undertook a cross-sectional survey on the work-related well-being of ATSS at the UWI, St. Augustine campus. Data were analyzed through the use of inferential statistics that allow for the analysis of differences (t-test and correlations) and others that explore the relationship or association between the independent factors and work-related well-being (correlations and regression). Findings revealed that there were no direct relationship between trade union involvement and the well-being of workers. However, the findings also showed that trade union involvement was directly related to the levels of motivation among employees and their perception of social support. Younger employees with higher educational qualifications had lower perceptions of the involvement of the trade unions. Findings also revealed that perceptions of social support were also related to their perceptions of job demand and resources, and directly with workers well-being. Female ATSS had higher mean scores on well-being. Job resources and demands were the only two factors that had predictive value in the understanding of work-related well-being among UWI-ATSS. Implications of these for theory, research and institutional policies are also discussed
Keywords: Work -- Psychological aspects -- Research -- Trinidad and Tobago; Work -- Social aspects -- Research -- Trinidad and Tobago; Employees -- Social aspects -- Trinidad and Tobago; Employees -- Mental health -- Trinidad and Tobago; Well-being -- Social aspects -- Research -- Trinidad and Tobago; Psychology, Industrial -- Research -- Trinidad and Tobago